Modeling And Analysis Of Composite Hinge For Aircraft Spoiler Using Finite Element Analysis - Wai, Chee Mun (2014)
This thesis is concerned with the modeling and analysis of a composite hinge bracket for Airbus A320 aircraft using Finite Element Method. The increasing demand of composite materials in aircraft structural design is due to the high strength and stiffness to weight ratio of the composite materials. The reduction in structural weight by the composite materials reduces the fuel consumption of the aircraft. Since the hinge bracket of the A320 aircraft is made of metallic materials, this research aims to redesign the hinge bracket with laminated composite plates. However, the design of structures with composites is not as easy as the design of metallic structures. Composites are heterogeneous and anisotropic in nature thus, complicating the structural analysis. The best practice of laminated composite design in the industry is simplified to accommodate the limitation of this research. The simplified design process is a simple three stages design process which focused on using Finite Element Anlysis for unidirectional laminated composite structural design. It begins with the determination of stress distribution in a metallic structure. The stress distribution allows the designer to identify areas of different stress distribution of the structure. Once the areas are identified, the direction of principle stresses is determine to decide on the fiber orientation and stacking sequence of the composite laminates for each area. Finally, the analysis of the laminated composite structure is carried out using Classical Laminate Plate theory and the structural integrity is accessed by the calculation of margin of safety. The simplified design process has been applied to redesign the metallic hinge bracket of A320 aircraft using IM7/8552 composite laminates. MSC Patran/Nastran and Abaqus CAE were used to carry out the finite element analysis of the hinge bracket. The composite hinge bracket has a margin of safety of 0.041. The weight savings by this composite hinge bracket is estimated to be 42.29 percent of the original metallic hinge bracket of A320. The success of this composite hinge design has proven that the simplified design process proposed in this research is indeed feasible for the purpose of preliminary design of laminated composite structures. The advantage of this simplified design process is that it approaches the design of composite structures in a systematic manner thus, allowing the identification of factors influencing the strength the laminated composite structural design. Since it is based on Finite Element Method, the results are at best approximations but sufficient to boost the level of confidence in the preliminary design stage.